The Implementation of Application Kahoot in Learning Process - Rosita, Reni (Universitas Sebelas Maret, 2022)
Increasing the educational quality is a continually process to be done by the teacher. It is hoped that a teachers today have an ability in self adaptation at the technology advance and modify their learning with the up to date media such as application. This paper is aimed at to identify the application of Kahoot in learning process and to know whether Kahoot applicaton is effective in supporting the learning process. Based on the literature review, it can be drawn a conclusion that increasing the education quality should be along with the technology advance. The application of Kahoot is an example of the application that can be used to present the assessment sheet in form of digital educational game. This application is a constructive device. It also implies a change to the children perception about the learning they have. As the result, the learning process is exciting for them.